Acute graft versus host disease 1976–2020: reduced incidence and predictive factors - Di Francesco, Alessandra; Raiola, Anna Maria; Dominietto, Alida; Di Grazia, Carmen; Gualandi, Francesca; Van Lint, Maria Teresa; Bregante, Stefania; Chiusolo, Patrizia; Laurenti, Luca; Sora, Federica; Giammarco, Sabrina; Metafuni, Elisabetta; et al. (Frontiers in Medicine, 2024)
We studied the incidence of acute graft versus host disease (GvHD) and its outcome in three consecutive time frames (year <2000; 2000–2010; >2010), in 3,120 patients allografted in two transplant Centers between 1976 and 2020. The median age increased over the three periods from 32 to 42 to 54 years (p < 0.00001). The median day of onset of GvHD in the three periods was day +14, day +16, and day +30, respectively (p < 0.0001). The cumulative incidence (CI) of GvHD grades II–IV in the three periods was 47, 24, and 16%, respectively (p < 0.00001). The CI of GvHD grades III–IV was 13, 5, and 4% (p < 0.001). In multivariate analysis, significant predictive factors for GvHD II–IV, on top of year of transplant, were anti-thymocyte globulin (ATG) (RR 0.67, p > 0.001); post-transplant cyclophosphamide (PTCY) (RR 0.41, p < 0.001), a family mismatched donor (RR 1.31, p = 0.03) a matched unrelated donor (RR 2.1, p < 0.001), an unrelated mismatched donor (RR1.8, p = 0.001), donor age above 40 years (RR 1.27, p < 0.001), hematological malignancy—as compared to aplastic anemia (RR 2.3, p < 0.001). When selecting only GvHD grade II, in a multivariate analysis, there was a significant reduction of transplant-related mortality (TRM) for patients grafted in 2001–2010 (RR 0.62, p < 0.0001) and for patients grafted in 2011–2020 (RR 0.35, p < 0.0001) as compared to grafts before the year 2000. A similar reduction in time was seen for patients with GvHD grades III–IV. The overall TRM in the three periods was 30, 22, and 16% (p < 0.0001) and survival was 47, 51, and 58% (p < 0.0001). Relapse risk was unchanged. In conclusion, we showed improved prevention of acute GvHD with time, together with a significant delay in the onset of the disease. Treatment of GvHD has also improved over time, as suggested by both reduced TRM and improved survival in more recent transplant periods.